2006
DOI: 10.2166/wh.2006.050
|View full text |Cite
|
Sign up to set email alerts
|

Field scale quantification of microbial transport from bovine faeces under simulated rainfall events

Abstract: The dispersion and transport of Cryptosporidium parvum oocysts, Escherichia coli and PRD1 bacteriophage seeded into artificial bovine faecal pats was studied during simulated rainfall events. Experimental soil plots were divided in two, one sub-plot with bare soil and the other with natural vegetation. Simulated rainfall events of 55 mm.h(-1) for 30 min were then applied to the soil plots. Each experimental treatment was performed in duplicate and consisted of three sequential artificial rainfall events ('Runs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 34 publications
5
36
0
Order By: Relevance
“…Stock titers were determined by the DAL method. Both MS2 and PRD1 were selected because of their prior use as surrogates for enteric viruses, such as NoV and human adenoviruses, respectively (8,12). MNV (type 1) and FCV (strain F9) stocks were propagated in monolayers of RAW 264.7 (ATCC TIB-71) and Crandall Reese feline kidney (CrFK) cells, as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Stock titers were determined by the DAL method. Both MS2 and PRD1 were selected because of their prior use as surrogates for enteric viruses, such as NoV and human adenoviruses, respectively (8,12). MNV (type 1) and FCV (strain F9) stocks were propagated in monolayers of RAW 264.7 (ATCC TIB-71) and Crandall Reese feline kidney (CrFK) cells, as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…The additional viral surrogates used in the present study, including PRD1 and MNV-1, have not been used in published studies involving UF of 100-liter environmental water samples. The bacteriophage PRD1 was chosen here as a suitable surrogate for the study of HuAdVs (12). Similar to HuAdVs, PRD1 is a 63-nm, icosahedral virus with double-stranded DNA, making it an appropriate model.…”
mentioning
confidence: 99%
“…Yu et al (2013) reported greater retention of latex microspheres to surface vegetation occurred at higher IS and for larger particles. Ferguson et al (2007) found that larger microorganisms (Cryptosporidium and E. coli) were more efficiently removed from runoff water than smaller microbes (coliphage PRD1) in field studies. Furthermore, previous studies have not yet modeled the full dynamics of water flow and microbial transport in runoff water and soil.…”
Section: Introductionmentioning
confidence: 93%